Assessing COVID-19-related anxiety and functional impairment amongst nurses in Malawi - Genesis Chorwe-Sungani (AOSIS, 2021)
Background: Psychological well-being of nurses is crucial for them to effectively discharge their duties. However, coronavirus disease 2019 (COVID-19)-related anxiety can interfere with nurses' performance and reduce their self-efficacy. Aim: The primary aim of this study was to assess COVID-19-related anxiety and functional impairment amongst nurses in Malawi. The secondary aim of the study was to determine reliability and validity of the Coronavirus Anxiety Scale. Setting: The study was conducted in Malawi. Methods: This was a cross-sectional study that collected quantitative data from 102 nurses in Malawi online. Data were analysed using descriptive statistics and receiver operating curve analysis. Results: This study found that 25.5% (26) of respondents had COVID-19-related anxiety and 48% (49) functional impairment. There were significant differences in the numbers of respondents who had functional impairment in relation to workplace (Χ2 = 8.7, p = 0.03), with many of those working in hospitals (58.6%, n = 34) having highest levels (mean = 20.6 ± 10.4). The Coronavirus Anxiety Scale proved to be an effective instrument (Sensitivity = 73.1%; Specificity = 60.5%; area under the curve = 0.73) for assessing COVID-19-related anxiety amongst nurses. Conclusion: It is necessary to screen nurses for COVID-19-related anxiety and functional impairment and provide them effective psychosocial interventions. Policymakers should place more emphasis on allocation of financial resources to mental health services and staff support programmes targeting nurses during pandemics. There is a need to conduct future research on mental health interventions that might be used to assist nurses with COVID-19-related anxiety and functional impairment.